KEBERADAAN POLITIK KEKERABATAN DALAM KONSEP NEGARA HUKUM PANCASILA - Muslikhah, UMI (UIR Law Review, 2022)
The 1945 Constitution of the Republic of Indonesia (UUD) Article 1 paragraph (3) states that "The Indonesian state is a state of law" so that it can be clearly explained that Indonesia is a state of law, not a Machtsstaat state which is based on mere power, the existence of dynasties. Politics in the Indonesian constitutional system has recently become a very disturbing phenomenon. In the development of political dynasties in Indonesia with a pattern of centralizing power in certain families or relatives, it can kill the potential of other citizens who have integrity and credibility as leaders in the region and the democratic process does not run healthily and fair play.